RESEÑA de: Duran, C. (ed.) Correspondència entre Àngel Guimerà i Jaume Ramon i Vidales, 1865-1898, Lleida, Punctum, 2016, 270 pp. - Camps Arbós, Josep (Revista de lenguas y literaturas catalana, gallega y vasca, 2018)
-